Diversity Of Products, Places, Promotion On Purchase Decisions Of Ud Martabe Merauke Customers - Noer, Elly; Esy Lewaherilla (Pascasarjana, Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2023)
The writing of this research article is done to see how big the factor of product diversity, place and sales promotion is on the purchasing decisions of UD Martabe customers on Jl Sultan Syarir Merauke. . The population in this study are those who are customers of UD Martabe. The sample is 100 respondents and the sampling technique used is incidental sampling technique. The types and sources of data used in this study are the types of primary data and secondary data. The data collection methods used are observation, interviews and the provision of questionnaires or questionnaires. Researchers will perform data analysis techniques using research instrument tests (validity test and reliability test), Classical Assumption Test, Multiple Regression Analysis, Hypothesis Testing (T Test, F Test and Determination Test) using the help of Statistical Product and Service Solution (SPSS) software.The results of the analysis show that the diversity of products, places and promotions has an influence that the independent variables in this case the variables of product diversity (X1), place/location (X2), and promotions (X3) have a positive and significant influence on purchasing decisions at UD Martabe Merauke. Keywords: Purchase Decision, Product Diversity, Promotion, Place